Collective wisdom co-creating media for equity and justice - Cizek, Katerina; Uricchio, William 1952- (The MIT Press, 2022)
"Collective Wisdom tracks co-creation in media-making, efforts that reach beyond limits of singular authorship, an ancient and under-documented practice"--
Bibliographie: Seite 339-359
Keywords: Medien; Kooperation; Crowdsourcing; Mass media / Authorship; Creation (Literary, artistic, etc.); Artistic collaboration; Social justice; Social Justice; Collaboration artistique; Justice sociale; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Aufsatzsammlung